Jugulo-atrial Bypass Procedure in Malignant Mediastinal Tumor with Superior Vena Cava Syndrome (SVCS) at Sanglah General Hospital, Bali, Indonesia: Case Series - I Nyoman Semadi (Journal of Global Pharma Technology, 2020)
Background: Superior vena cava syndrome (SVCS) is a collection of symptoms and signs due to obstruction in the superior vena cava (SVC). More than 90% of SVCS cases are caused by malignancy (lung, breast, intra-mediastinal organs) and vascular reconstruction surgery is the last resort in the management of SVCS. Decompression surgery still can be performed on all types of tumours. These case series aim to elaborate on the outcome of the jugulo-atrial bypass procedure in malignant mediastinal tumour with SVCS at Sanglah General Hospital, Bali, Indonesia. Case Description: In Case 1, Male 31-year-old, has chief complaint shortness of breathing accompanied by swelling on face, neck, and chest that has become worse since one month prior to admitted to the Sanglah General Hospital. A similar clinical finding was also found in Case 2, Male 53-year-old, with a productive dry cough and coughing up blood for more than two months and revealed an anterior mediastinal mass on CT-Scan. However, in Case 3 Male 68-year-old, his shortness of breath began after the history of lump on neck since 3 years ago. He was also diagnosed with the antiphospholipid syndrome and received oral anticoagulant therapy for 17 months. The sagittal, coronal, and axial view of chest CT scan with contrast showed an apparent demarcated heterogeneous mass in the anterior mediastinum with central necrosis. The calcification component was also found as a resulted in vena cava superior suppression on each case. The operative procedure was a median sternotomy with jugulo-atrial bypass procedure and followed by chemotherapy. The complete resolution of the anterior mediastinal mass as well as the improvement of clinical outcome were exhibited few weeks after treatment. Conclusion: Two of the three cases of malignant mediastinal tumour have been performed jugulo-atrial bypass surgery to reduce SVCS. From the histopathological examination, these three cases with SVCS were malignant mediastinal tumour. Jugulo-atrial bypass procedure was proven to reduce complaints of shortness of breath and swelling post-surgery. Keywords : SVCS, Malignant Mediastinal Tumor, Jugulo-Atrial By-Pass.